Sexual Harassment in the Work Place: A Case in Pakistan - Ahmad, Sadaf (Review of Women's Studies; Vol 11 No 1-2 (2001): Review of Women's Studies Volume XI, Numbers 1-2 (January-December 2001))
This paper attempts to provide an overview of sexual harassment in the work place in the Pakistani context. It will also report results of a case study of an incident of sexual harassment reported by a group of women working in a multi-national organization.